2014
DOI: 10.1007/978-3-319-13488-8_20
|View full text |Cite
|
Sign up to set email alerts
|

Detection of DNS Traffic Anomalies in Large Networks

Abstract: Abstract. Almost every Internet communication is preceded by a translation of a DNS name to an IP address. Therefore monitoring of DNS traffic can effectively extend capabilities of current methods for network traffic anomaly detection. In order to effectively monitor this traffic, we propose a new flow metering algorithm that saves resources of a flow exporter. Next, to show benefits of the DNS traffic monitoring for anomaly detection, we introduce novel detection methods using DNS extended flows. The evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…In the approach, a destination can become trusted by transitivity, if its origin can be evaluated by another trusted entity. The main contribution of [16] was an algorithm that performs DNS trafc monitoring in large networks based on the extension of standard fows. The authors in [15] presented NEMEA, a modular framework for network trafc analysis at Layer 7 that uses the stream-wise concept, i. e. data is analysed continuously in the memory with minimal data storage required.…”
Section: Flow-based Analysismentioning
confidence: 99%
“…In the approach, a destination can become trusted by transitivity, if its origin can be evaluated by another trusted entity. The main contribution of [16] was an algorithm that performs DNS trafc monitoring in large networks based on the extension of standard fows. The authors in [15] presented NEMEA, a modular framework for network trafc analysis at Layer 7 that uses the stream-wise concept, i. e. data is analysed continuously in the memory with minimal data storage required.…”
Section: Flow-based Analysismentioning
confidence: 99%
“…Yuchi et al [42] investigated DNS anomalies in the context of Heap's law stating that a corpus of text containing N words typically contains on the order of cNβ distinct words, for constant c and 0<β<1. Cermák et al [43] identified that only four DNS packet fields are useful for most of the DNS traffic analyzing methods: queried domain name, queried record type, response return code and response itself. They use the concept of standard flow and extended flow to detect DNS attacks on large networks.…”
Section: Dns Anomalies Identificationmentioning
confidence: 99%
“…Yuchi et al [7] investigated DNS anomalies in the context of Heap's law stating that a corpus of text containing N words typically contains on the order of cN β distinct words, for constant c and 0<β<1. Cermák et al [8] identified that only four DNS packet fields are useful for most of the DNS traffic analzing methods: queried domain name, queried record type, response code and IP address returned. Yarochkin et al [9] presented an open source DNSPACKETLIZER tool to analyze DNS traffic in-real time.…”
Section: Related Workmentioning
confidence: 99%